One day in May : 24 hours in the life of Indiana. (Indiana University Press : Quarry Books, 2016)
On May 20, 2016, armed with only their cameras, Hoosiers set out to capture the nature of their state and its people--from farmyards to city streets, state parks to suburbs, the familiar to the surprising--and in the process document a rich and diverse culture in the everyday. In these remarkable photographs, Hoosiers reclaim their state and define their identity, visually guiding readers through 24 hours of life in Indiana. Over 140 photographs preserve the wealth of their experiences and the strength of their love for their families, communities, and heritage.